Assessing firesetters with intellectual disabilities. Issue 4 (3rd December 2019) - Taylor, John L.; Thorne, Ian
Abstract : Purpose: People with intellectual disabilities who set fires are a heterogeneous and clinically complex group who present significant challenges to the wider community and to forensic practitioners working in forensic mental health and correctional settings. There is little available in the literature to support professionals when considering assessment and formulation for clients exhibiting these perturbing behaviours. The paper aims to discuss this issue. Design/methodology/approach: In this paper the materials available to assist forensic practitioners in considering assessment and formulation of people with intellectual disabilities who set fires are described and outlined. Findings: An assessment scheme is proposed for organising information from a variety of sources to assist professionals in understanding the nature of risks and clinical needs of firesetters with intellectual disabilities. A newly revised risk assessment measure designed for this population is provided. Practical implications: Forensic practitioners are provided with a framework and tools to assist with their assessment and formulation of firesetters with intellectual disabilities. Originality/value: This is the first time a newly revised risk assessment for firesetting behaviour by people with intellectual disabilities has been presented.